Correlating instrumental and sensory analyses of flavour - Langridge, James P. (2004)
The relationship between in vivo captured data from an atmospheric pressure chemical ionisation mass spectrometer (APCI-MS) and sensory/psychophysical analyses was investigated. The stimuli used were mainly single volatiles under gas phase control or calibration by development of different olfactometry methods.